Real Exchange Rates and Productivity : Closed-Form Solutions and Some Empirical Evidence - Zaman, Jahanara (IMF Working Papers; Working Paper, 2000)
This paper examines the impact of productivity shocks on real exchange rate fluctuations in a dynamic international general equilibrium model with nontraded goods. The model predicts a close association between relative technology shocks and bilateral real exchange rate movements. Empirical results based on the data for Group of Seven countries are consistent with the predicted theoretical correlations. Using Johansen and Juselius (1990) multivariate cointegration tests the study finds that a statistically significant relationship exists between bilateral real exchange rates and international productivity differentials in the traded and nontraded sectors.